(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Self-directed learning (SDL), is an essential concept in learning, and, in a more extensive sense, student-centered learning. Considering the sophisticated nature of SDL, it has been underestimated and given a superficial meaning, i.e. self-study. With specific end goal to build up a deeper understanding and make utilization of the potential in SDL, this study discusses and puts forward a more significant meaning. The current study is an attempt to investigate Iraqi EFL college student’s self-directed learning in English, thus the study aims at: 1-Investigating Iraqi EFL college students’ self-directed learning in English, 2-Finding out the differences among the aspects of self-directed learning. Two hypotheses have been tested as follows: 1-Iraqi EFL college students are not able to use self-directed learning abilities in learning English. 2-There are no statistically significant differences among the aspects of self- directed learning. The random sample of the current study consists of 132 students from the four academic stages of the English Department at College of Education for Humanities / University of Diyala, for the academic year (2015-2016). Four aspects of self-directed learning, namely ; General beliefs / Attitudes , planning , practice and social communication aspects are concerned. In order to achieve the aims of this study and to assess its hypotheses , a questionnaire has been constructed for data gathering .The questionnaire covers eight scales that contain (39) items .The following four domains are : General beliefs / Attitudes (4) items , planning (18) items , practice (11) items and social communication (6) items. The questionnaire is exposed to a jury of experts for the purpose of ascertaining its validity. Two methods are applied to calculate the questionnaire reliability coefficient.